El uso de celular y su incidencia en las relaciones interpersonales de la comunidad educativa "Gabriel García Moreno" parroquia García Moreno- Cotacachi-Ecuador 2020-2021. - Lita, Eliana E. (2022)
The objective of this research was to identify the incidence generated by the use of the cell phone in the interpersonal relationships of the Gabriel Garcia Moreno educational community and to determine the consequences and implications of the use of mobile telephony in daily life. In this study, the scientific method was applied with a mixed approach, which helped to deepen its incidents and how cell phone use can affect interpersonal relationships, the research is descriptive - documentary and the survey was used to collect data. Information. The population under study was 28 teachers, 115 students and 83 high school parents from the “Gabriel Garcia Moreno” Educational Unit. The results show that students use the mobile device for an average of 1 to 3 hours a day, and the use is limited to social networks, recreation and academic activities, while teachers use the mobile device for an average of more than 5 hours and use is limited to academic and work activities, and parents use an average of 1 to 3 hours a day and its use is limited to surfing the internet, looking for information and phone calls. Regarding interpersonal relationships, this research does not find negative results that affect members of the educational community. The conclusions of this research are that the mobile device is essential for academic and work activities and its use does not present significant problems in interpersonal relationships between members of the educational community.